SIKAP PROFESIONAL PENDIDIKAN BAHASA INDONESIA SEBAGAI PENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Ika Mustika (Jurnal Semantik, 2013)
Almost all countries put education as a priority in the context of nation building. Similarly, the nation and state of Indonesia placed education as a strategic value to the advancement of the nation. The passing of the curriculum changes to the curriculum in 2013 SBC 2006 is a real effort on the part of the government to improve the quality of education in Indonesia. Indeed the 2013 curriculum is structured to prepare students to face the challenges of an increasingly complex future. Support of various stakeholders, especially educators is necessary for successfully implementing the curriculum in 2013 in accordance with the plans that have been well established. Therefore, educators as a front line that are directly related to the implementation of the educational program are required to have the readiness and willingness to work in a professional manner. Of course the demands of professional educators should be addressed by improving the qualifications and competence of educators. Moreover, in this era of globalization, the challenges and responsibilities of educators increasingly complex. This paper presents a simple thought about the professional attitude that must be owned by Indonesian educators, especially educators so that they can print learners adaptive to the changing times in accordance with the demands of the curriculum in 2013.Keywords: AttitudesProfessionals, EducatorsIndonesian, Curriculum2013